PENGARUH KREATIVITAS DAN PENGEMBANGAN KARYAWAN TERHADAP KEPUASAN KERJA DI PT. XYZ - Sutopo, Israel Eko Bima; Susanto, Andi Heru (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
This study aims to analyze the influence of creativity and employee development on job satisfaction at PT. XYZ. The background of the study emphasizes the importance of quality employees, who have the skills and abilities to complete the work well and continue to improve these abilities consistently. Therefore, this study highlights the importance of an effective management strategy, which not only pays attention to salary aspects but also fairness, management support, and a collaborative work environment to improve employee welfare. This study uses a quantitative approach with an online survey technique. Data were collected from 297 respondents who were samples from a population of 2,000 employees at PT. XYZ. Data analysis used multiple linear regression analysis to test the effect of independent variables (creativity and employee development) on the dependent variable (job satisfaction). The results showed that creativity had a negative and significant effect on job satisfaction. Conversely, employee development had a positive and significant effect on job satisfaction. Simultaneously, these two independent variables were significantly related to job satisfaction. The conclusion of this study is that a holistic and sustainable management strategy is essential in ensuring high job satisfaction at PT. XYZ, which ultimately supports the growth and sustainability of the company.